199TiPPhase III (COSMIC-312) study of cabozantinib (C) in combination with atezolizumab (A) vs sorafenib (S) in patients (pts) with advanced hepatocellular carcinoma (aHCC) who have not received previous systemic anticancer therapy. (24th November 2019) - Yau, T; Rimassa, L; Cheng, A-L; Park, J-W; Braiteh, F; Chaudhry, A; Benzaghou, F; Thuluvath, P; Hazra, S; Milwee, S; Tan, B; Sinha, R; et al.
Abstract: Background: C inhibits tyrosine kinases involved in tumor growth, angiogenesis, and immune regulation, including MET, VEGFR, and TAM kinases (Tyro3, AXL, MER). C is approved in the United States and Europe for treatment of aHCC after prior S based on improved overall survival (OS) vs placebo in the phase 3 CELESTIAL trial (Abou-Alfa NEJM 2018). C may promote an immune-permissive tumor environment, which could enhance response to immune checkpoint inhibitors. C is being evaluated in combination with the anti-PD-L1 antibody A in multiple tumor types including HCC in a phase 1 study; recommended dose, preliminary clinical activity, and safety of the combination have been established in aRCC (Agarwal Ann Oncol 2018). A in combination with bevacizumab, an anti-VEGF antibody, has shown preliminary clinical activity in first-line aHCC (Pishvaian Ann Oncol 2018). Here, we present the study design of a phase 3 trial of C + A vs S in pts with aHCC who have not received prior systemic therapy. Trial design: This global, randomized, open-label phase 3 trial (NCT03755791) is evaluating the efficacy and safety of C + A vs S as first-line treatment for aHCC. C vs S will also be evaluated as a secondary endpoint. Eligibility criteria include age ≥18 years, BCLC stage B or C, Child-Pugh A, ECOG PS ≤ 1, and measurable disease per RECIST 1.1. Pts are randomized 2:1:1 to an experimental arm of C (40 mg qd) + A (1200 mg infusion q3w), a control arm of S (400 mg bid), and a C monotherapy arm (60 mg qd). 740 pts are planned to be enrolled at ∼250 sites globally. Randomization is stratified by disease etiology (HBV [with or without HCV], HCV [without HBV], or other), region (Asia, other), and the presence of extrahepatic disease and/or macrovascular invasion (yes, no). OS and progression-free survival (PFS) for C+A vs S are primary endpoints, and PFS for C vs S is a secondary endpoint. Additional endpoints include safety, pharmacokinetics, and correlation of biomarker analyses with clinical outcomes. The first patient was enrolled in December 2018, and enrollment is ongoing. Clinical trial identification: NCT03755791 (Other Study ID Numbers: XL184-312). Legal entity responsible for the study: Exelixis. Funding: Exelixis. Disclosure: T. Yau: Advisory / Consultancy: Exelixis; Honoraria (self): Ipsen, Exelixis. L. Rimassa: Advisory / Consultancy: Lilly, Bayer, Baxter, Sirtex Medical, Italfarmaco, Sanofi, ArQule, Baxter, Ipsen, Exelixis, Amgen, Celgene, Eisai, Hengrui, MSD; Honoraria (self): AstraZeneca, AbbVie, Gilead, Roche; Travel / Accommodation / Expenses: ArQule, Ipsen. A-L. Cheng: Advisory / Consultancy, Advisory Board: Bayer Schering Pharma, Bristol-Myers Squibb, Eisai, Merck Serono, Novartis, Ono Pharmaceutical, Exelixis, Nucleix Ltd., Roche/Genentech, and IQVIA; Advisory / Consultancy, Consultancy: Bayer Schering Pharma, Bristol-Myers Squibb, Eisai, Merck Serono, Novartis, Ono Pharmaceutical, Exelixis, Nucleix Ltd., Roche/Genentech, and IQVIA; Honoraria (self): Bayer, Eisai, and Merck Sharp Dohme, Merck Serono, Novartis, Ono Pharmaceutical, Roche/Genentech, and IQVIA. J-W. Park: Advisory / Consultancy, Advisory board: Astra-Zeneca, Ono, BMS, Bayer, Midatech; Research grant / Funding (self): Ono-BMS, AstraZeneca, Blueprint, Roche, Eisai, Exelixis, Kowa; Advisory / Consultancy, Consultancy: Ono, Genetech, Roche, BMS, Bayer, Ipsen; Honoraria (self): Bayer, Ono, Eisai. F. Braiteh: Shareholder / Stockholder / Stock options: Agios; Bristol-Myers Squibb; Clovis Oncology; Insys Therapeutics; Tesaro; Honoraria (self): Abbott Nutrition; Amgen; ARIAD; AstraZeneca; Bayer; Boehringer Ingelheim; Bristol-Myers Squibb; Celgene; Genentech/Roche; HERON; Incyte; Insys Therapeutics; Insys Therapeutics; Ipsen; Lexicon; Lilly; Taiho Pharmaceutical; Advisory / Consultancy: Ambry Genetics; Amgen; AstraZeneca; Bayer; Boehringer Ingelheim; Bristol-Myers Squibb; Celgene; Clovis Oncology; Genentech/Roche; Incyte; Insys Therapeutics; Ipsen; Ipsen; Lexicon; Lilly; Merck; Merrimack; Pfizer; Regeneron; Sanofi; Speaker Bureau / Expert testimony: Amgen; AstraZeneca; Boehringer Ingelheim; Bristol-Myers Squibb; Celgene; Genentech/Roche; Incyte; Insys Therapeutics; Ipsen; Lilly; Merck; Merck; Merrimack; Pfizer; Taiho Pharmaceutical; Travel / Accommodation / Expenses: - Amgen; AstraZeneca/MedImmune; Bayer; Bayer/Onyx; Boehringer Ingelheim; Bristol-Myers Squibb; Celgene; Clovis Oncology; Exelixis; HERON; Incyte; Insys Therapeutics; Ipsen; Lexicon; Merrimack; Novartis; Pfizer; Regeneron; Roche/Genentech; Sanofi; Taiho Ph. F. Benzaghou: Full / Part-time employment: IPSEN; Shareholder / Stockholder / Stock options: IPSEN. P. Thuluvath: Honoraria (self): AbbVie; Gilead Sciences; Advisory / Consultancy: AbbVie; Eisai; Gilead Sciences; Speaker Bureau / Expert testimony: AbbVie; Gilead Sciences; Research grant / Funding (institution): AbbVie (Inst); Allergan (Inst); Conatus (Inst); Cymabay Therapeutics (Inst); Eisai (Inst); Sillajen (Inst); Target Pharmasolutions (Inst); Tobira Therapeutics (Inst); Zydus Pharmaceuticals (Inst). S. Hazra: Full / Part-time employment: Exelixis; Shareholder / Stockholder / Stock options: Exelixis. S. Milwee: Full / Part-time employment: Exelixis; Shareholder / Stockholder / Stock options: Exelixis. B. Tan: Research grant / Funding (institution): Exelixis. A.X. Zhu: Advisory / Consultancy: AstraZeneca; Bayer; Bristol-Myers Squibb; eisai; Exelixis; Lilly; Merck; Novartis; Sanofi; Research grant / Funding (institution): Bayer (Inst); Bristol-Myers Squibb (Inst); Lilly (Inst); Merck (Inst); Novartis (Inst). R.K. Kelley: Advisory / Consultancy, funding to institution: Agios, AstraZeneca, Bayer, BMS ; Advisory / Consultancy, funding to self: IDMC: Genentech/Roche ; Research grant / Funding (institution): Agios, AstraZeneca, Bayer, BMS, Eli Lilly, Exelixis, EMD Serono, Medimmune, Merck, Novartis, QED, Taiho. All other authors have declared no conflicts of interest.